Does Manipulation under Anesthesia Increase the Risk of Revision Total Knee Arthroplasty? A Matched Case Control Study - Pierce, Todd P.; Issa, Kimona; Festa, Anthony; Scillia, Anthony J.; McInerney, Vincent K.; Mont, Michael A. (The Journal of Knee Surgery, 2017)
Manipulation under anesthesia (MUA) can help patients regain an adequate range of motion (ROM) following total knee arthroplasty (TKA). Although there are studies reporting that MUA can assist in improving ROM, there is a paucity of studies regarding whether requiring an MUA is associated with an increased risk of revision. The purpose of this study was to assess the: (1) incidence of revision TKA and (2) outcomes of those undergoing MUA and compare it with a matched cohort who did not require MUA. A prospectively collected database of two high-volume institutions was assessed for patients who required a single MUA following TKA between 2005 and 2011. We found a total of 138 knees with a mean 8.5-year follow-up post-MUA. We compared this with a matched cohort (1:1) who underwent TKA during this same time period but did not require an MUA. Incidence of revision surgery and clinical outcomes were compared between the two cohorts. Within the MUA cohort, nine knees underwent revision, which was similar to the matched cohort that had seven revisions (93 vs. 95%; p = 0.6). The mean KSS-functional (88 vs. 90 points; p = 0.15) and clinical scores (87 vs. 89 points; p = 0.1) were similar between the two cohorts. Undergoing an MUA was not associated with an increased risk of revision TKA. If patients require MUA, they may still achieve satisfactory outcomes. This information can be used in educating patients so they may be able to formulate their expectations following their MUA.
Keywords: revision total knee arthroplasty; manipulation under anesthesia; complications; stiffness